Community structure of zooxanthellate corals (Anthozoa: Scleractinia) in Carrizales coral reef, Pacific coast, Mexico - Reyes Bonilla, Héctor (2013)
Community structure of zooxanthellate corals (Anthozoa: Scleractinia) in Carrizales coral reef, Pacific coast, Mexico. Coral reefs in the Mexican Pacific and notably those of the continental coastline of Colima state are still poorly studied. Fortunately, recent efforts have been carried out by researchers from different Mexican institutions to fill up these information gaps. The aim of this study was to determine the ecological structure of the rich and undisturbed coral building communities of Carrizales by using the point transect interception method (25m-long). For this, three survey expeditions were conducted between June and October 2005 and September 2006; and for comparison purposes, the reef was subdivided according to its position in the bay, and depth (0 to 5m, and 6 to 10m). Thirteen coral species were observed in the area, with Pocillopora verrucosa as the most abundant, contributing up to 32.8% of total cover, followed by Porites panamensis and Pocillopora capitata with 11% and 7%, respectively. Other species, Pocillopora damicornis, Pavona gigantea, Pocillopora eydouxi and Pocillopora inflata accounted for 1.5% to 2% of coral cover whereas the remaining five species had cover of less than 1%. Seven of the observed species represented new records for Colima state coastline: Pocillopora eydouxi, P. inflata, P. meandrina, Pavona duerdeni, P. varians, Psammocora stellata and P. contigua. This last species is a relevant record, because it has never been observed before in the Eastern Pacific. Although there was no significant difference (ANOVA, p=0.478) neither in the abundance between the sides of the bay, nor between the depths considered, and the shallow zone observed the higher coral cover. Live coral cover was up to 61%, one of the highest ever reported for the Mexican Pacific, including the Gulf of California. The observed values of diversity (H´=0.44±0.02), uniformity (J´=0.76±0.02), and taxonomic distinctness index (Δ*=45.87±3.16), showed that currently this is the most important coral reef of Colima coastline. Currently, this region does not show any disturbance effects, but the increasing economic development of Manzanillo, as one of the main commercial ports of Mexico, its proximity to the reef, and the burgeoning number of tourists, may have some ecosystem impacts, for which management and conservation plans for Colima coastline are highly recommended.